2008
DOI: 10.1080/00207450701777227
|View full text |Cite
|
Sign up to set email alerts
|

Right Brain is Important for Students’ Achievements in Science

Abstract: Relations between the hearing durations of right and left ears and points on the introductory examination for entrance to the Science School of Ataturk University in Erzurum were investigated in 31 male and 13 female students. The hearing duration of the left ear was significantly associated with the scores of the examination for the university entrance, the hearing duration for the right ear being not significantly related to the examination scores. The results suggest that the right brain would be beneficial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…They suggested that the positive effect of exercise must be associated with the right brain or left hand. Dogar, Dane, Dane, and Tan (2008) reported hearing durations in the left ear but not the right ear were associated with scores on an examination for university entrance in Turkey. They suggested that right brain might be important for students' achievements in science.…”
Section: Resultsmentioning
confidence: 94%
“…They suggested that the positive effect of exercise must be associated with the right brain or left hand. Dogar, Dane, Dane, and Tan (2008) reported hearing durations in the left ear but not the right ear were associated with scores on an examination for university entrance in Turkey. They suggested that right brain might be important for students' achievements in science.…”
Section: Resultsmentioning
confidence: 94%